Ez frozen / Luqman Hakim Muhaiyuddin ... [et al.] - Muhaiyuddin, Luqman Hakim; Dzulkafli, Emir Iqbal; Mohd Yahya, Muhammad Hazim; Mohd Alias, Muhd Arif Akmal; Jainal, Ahmad Fahmi; Yusaini, Danish Hazriq (2021)
The company is a limited liability partnership where the company is based on partnership between five peoples and each partner has designated position such as general manager, administration manager, marketing manager ad financial manager which suits their qualification and skills. The general manager will have more share percentage compared to other partnership members. This is to optimize a good management of the EZ Frozen. EZ Frozen also has another employee working as a promoter for the shop The mission of the company is to be one stop Halal frozen food solution provider and together improve the local brand of frozen food. Our business is located at Angsana Johor Bahru Mall which is near to a residential area, public school, mosque, community college, and this mall is a hot spot for Singaporean. Our marketing strategies can be divided by four which is promotion strategy, products strategy, place strategy and pricing strategies. For promotion strategy, our company is a business that markets its products mainly through social media platform such as Instagram, Whatsapp, Twitter and Facebook which help business to grow by providing business friendly features while for place strategy, the location is very strategic as it is at the centre shopping mall also located at the ground floor and near to main entrance and parking entrance. For pricing tactics, volume and unit selling strategy is used here customers also get discount price from our company if they buy in large quantities depending on the minimum amount of quantity. Lastly, for the product strategy, many of EZ Frozen products are mainly homemade foods and some are from Small & Medium Enterprise (SME).